Understanding the Role of Self-Efficacy in Mediating the Relationship Between Peer Support and School Engagement - Bennett, Laura; Moreau, Samuel; Matthews, Brian (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the mediating role of self-efficacy in the relationship between peer support and school engagement among high school students in Canada. A descriptive correlational research design was used to examine the proposed relationships. The sample included 440 Canadian high school students selected using the Krejcie and Morgan sample size table. Participants completed three standardized instruments: the Peer Support subscale of the Child and Adolescent Social Support Scale (CASSS), the Self-Efficacy Questionnaire for Children (SEQ-C), and the School Engagement Scale (SES). Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation, and AMOS-21 for Structural Equation Modeling (SEM) to test the mediating effect of self-efficacy. Descriptive statistics showed high levels of peer support (M = 4.41, SD = 0.57), self-efficacy (M = 3.88, SD = 0.63), and school engagement (M = 4.12, SD = 0.52). Pearson correlations indicated significant positive associations between peer support and self-efficacy (r = .47, p < .001), peer support and school engagement (r = .51, p < .001), and self-efficacy and school engagement (r = .62, p < .001). The SEM results showed good model fit (χ²/df = 1.93, CFI = 0.96, RMSEA = 0.046), and confirmed that self-efficacy significantly mediated the relationship between peer support and school engagement. The total effect of peer support on school engagement was significant (β = 0.56, p < .001), with both direct (β = 0.31, p < .001) and indirect effects through self-efficacy (β = 0.25, p < .001). The findings highlight the crucial role of self-efficacy as a psychological mechanism through which peer support enhances school engagement. These results emphasize the importance of fostering peer-connected environments and developing students’ self-beliefs to improve engagement outcomes in educational settings.